2015
DOI: 10.1002/cphc.201500383
|View full text |Cite
|
Sign up to set email alerts
|

Mechanofluorochromism of 1‐Alkanoylaminopyrenes

Abstract: To create a new series of mechanofluorochromic materials and to elucidate the mechanism of the phenomenon of mechanofluorochromism, 1-alkanoylaminopyrenes including 1-acetylaminopyrene (AAPy), 1-octanoylaminopyrene (OAPy), and 1-stearoylaminopyren (SAPy) were prepared. It was found that these materials exhibited mechanofluorochromism with emission colors in the crystalline samples changing reversibly from bluish purple to yellowish green, which could be induced by mechanical grinding. X-ray crystal structure a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 45 publications
0
24
0
Order By: Relevance
“…Because AIE‐active luminophores tend to form loosely‐packed assemblies, mechanical stimuli induces closed‐packing and/or conformational changes, which alter their photoluminescence properties. Another promising approach is the design of molecular structures in which different types of intermolecular interactions can compete against each other . Adopting this strategy, molecules can form several thermodynamically ( meta )stable assembled states and mechanical stimuli can induce interconversions among these states.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Because AIE‐active luminophores tend to form loosely‐packed assemblies, mechanical stimuli induces closed‐packing and/or conformational changes, which alter their photoluminescence properties. Another promising approach is the design of molecular structures in which different types of intermolecular interactions can compete against each other . Adopting this strategy, molecules can form several thermodynamically ( meta )stable assembled states and mechanical stimuli can induce interconversions among these states.…”
Section: Figurementioning
confidence: 99%
“…Adopting this strategy, molecules can form several thermodynamically ( meta )stable assembled states and mechanical stimuli can induce interconversions among these states. In particular, competition between hydrogen‐bonding and π–π stacking is effectively achieved by introducing amide groups directly into luminophores . This effectiveness is attributed to the fact that the length between amide groups forming hydrogen bonds is generally longer than the distance between aromatic groups forming π–π stacks.…”
Section: Figurementioning
confidence: 99%
“…Not only av ariety of simple molecular systems, but mechanochromic luminescents upramolecular systemsa nd self-assembled dyad molecule with dual sensitivity of photo-andm echanochromism have also been reported. [6] Nakano and co-workers have recently reported two series of mechanochromic luminescent materials [7,8] and demonstrated with as eries of diarylaminobenzaldehyde-based amorphous molecular materials that the mechanical inductiono fl arge conformational changes of excited molecules can give rise to mechanoresponsive luminescence. [7] As eries of mono-substituted pyrenesw as used to show that mechanochromic emission can be caused by formation of defects by grinding the crystalline samples, which allows for the excimer formation.…”
Section: Introductionmentioning
confidence: 99%
“…[7] As eries of mono-substituted pyrenesw as used to show that mechanochromic emission can be caused by formation of defects by grinding the crystalline samples, which allows for the excimer formation. [8] Molecular materials based on bis(cyanostyryl)benzene chromophores have also been widely exploited as basis for mechanoresponsive effects, because these molecules can adopta range of solid-state structurest hat give rise to multicolor emission. In as eries of studies, the Wederg roup hasb lended small amountso fb is(cyanostyryl)benzene derivatives with polymers and shown that tensile deformation leads to ab reakage of dye aggregates and, thus, ac hange from excimer-dominated to monomer-rich emission.…”
Section: Introductionmentioning
confidence: 99%
“…[14,[20][21][22][23] Regarding the emission in the solid state, variousk inds of mechanochromic illuminants based on pyrene derivates have been reported, which are accompanied by excimer-to-excimer,m onomer-to-excimer and conformation transitions. [24][25][26][27][28][29][30][31] Accordingly,i ti safacile and efficient method to use mechano-inducede xcimer emissiont oo btain excimer luminescence in the solid state.…”
Section: Introductionmentioning
confidence: 99%